Rút gọn biểu thức : $\frac{3√x}{x√x-1}$ -$\frac{1}{√x-1}$ =P

Question

Rút gọn biểu thức :
$\frac{3√x}{x√x-1}$ -$\frac{1}{√x-1}$ =P

in progress 0
Reese 1 năm 2021-08-09T02:00:36+00:00 1 Answers 9 views 0

Answers ( )

    0
    2021-08-09T02:01:46+00:00

    Bạn tham khảo:

    $P=\dfrac{3\sqrt{x}}{x\sqrt{x}-1}-$ $\dfrac{1}{\sqrt{x}-1}$

    $P=\dfrac{3\sqrt{x}}{(\sqrt{x}-1)(x+\sqrt{x}+1)}-$ $\dfrac{x+\sqrt{x}+1}{(\sqrt{x}-1)(x+\sqrt{x}+1)}$

    $P=\dfrac{3\sqrt{x}-x-\sqrt{x}-1}{y}$

    $P=\dfrac{-(x-2\sqrt{x}+1)}{(\sqrt{x}-1)}$

    $P=-\sqrt{x}+1$

    Học tốt

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )